The Influence of Cultural Competence on Nurse-Physician Collaboration in Diverse Healthcare Settings in KSA: A Qualitative Study - Tami Hlail Hazmi, Dr. Nasser Turki Aldhafeeri, Mohammed Khalif S Aldhafeeri, Turki Falah Turki Almutairi, Abdulhadi Hadyan Almutairi, Mohammed Thubayb Nasser Alsahli (Journal of International Crisis and Risk Communication Research, 2024)
Objective: This qualitative study aimed to explore the influence of cultural competence on nurse-physician collaboration in diverse healthcare settings in the Kingdom of Saudi Arabia (KSA), focusing on the perceptions and experiences of healthcare professionals. Methods: Semi-structured interviews were conducted with 20 participants, including 12 physicians and 8 nurses, working in various healthcare settings across KSA. Participants were recruited using purposive sampling, and data were analyzed using thematic analysis. Results: Four main themes emerged from the data: (1) understanding cultural differences, (2) effective communication strategies, (3) building trust and respect, and (4) organizational support for cultural competence. Participants emphasized the importance of cultural awareness, language proficiency, open communication, and a supportive work environment for effective nurse-physician collaboration in diverse healthcare settings. Conclusion: Enhancing cultural competence among healthcare professionals is crucial for improving nurse-physician collaboration in diverse healthcare settings in KSA. Policymakers and healthcare organizations should prioritize cultural competence training, language support, and organizational policies that foster a culturally inclusive work environment.